Ideology and Values in Turkey's Foreign Policy - V. A. Avatkov (Vestnik MGIMO-Universiteta)
The article considers the role of ideology and values in the formation and implementation of the current foreign policy of the Republic of Turkey. Taking into account the increasing role of regional actors such as Turkey in international politics, studying their tactics and mechanisms of influence on the global political environment is necessary to explain the further transformation of the international system.The study reveals the strengthening role of the ideology and values in world politics in general and in individual states, such as Turkey, in particular. Under the rule of the Justice and Development Party headed by the current President R.T. Erdogan the country began a gradual transition from «Kemalism», which includes the preservation of secularism, ProWestern democratic values and a gradual departure from the Ottoman heritage, to a more conservative domestic and foreign policy, characterized by the strengthening of Islamist and nationalist sentiments, as well as the transition to the policy of «neo-Ottomanism», «neo-pan-Turkism». The return of the idea of «aggrandizement» of the country to the official political discourse has affected the conduct of Turkey's foreign policy towards both the regional states and the world arena as a whole.The Republic not only began self-restoration as an autonomous actor of international relations in the eyes of the key world powers, but also started to spread its own values and ideas among the population of both the Middle East and among the states which constitute a national interest for Turkey (Russia, the post-Soviet space, etc.), thus influencing them at various levels and involving them in its orbit of influence – both politically, economically and from a humanitarian point of view.Using «hard power» abroad no longer meets the current Turkey’s policy. Instead it relies on forging humanitarian ties, combining initiatives in the cultural, educational and scientific fields to achieve a long-term influence. The Republic of Turkey is trying to spread the following values among the world community:«Justice». International relations must be just and fair. For Turkey it means conformity with its national interests.«Religious fatalism». Government actions both at home and abroad are legitimized through references to religion and fate.«Democratic values». The Republic of Turkey considers itself the most democratic state in the world and contrasts itself with “Western democracies”, which, according to the Turkish leadership, are spreading hegemony rather than democracy.«State-centrism» and collectivism. The interests of the state, society, and especially the Muslim Ummah, are placed above the values of the individual.«Traditional values». Given the Islamization and conservatism of Turkish society as a whole, traditional values also begin to play a major role in the general political discourse of the state.«Culture». Turkey also makes adjustments to the concept of «culture» in very inclusive terms, presenting its culture as a «melting pot» that can turn anything into Turkish.«Respect». In the eastern tradition, it is customary to show respect to elders, as well as neighbors and guests. Turkey uses a demonstration of respect in foreign policy instrumentally and pragmatically. An example of this is the address of the President of Turkey in relation to the leaders of other states: Nursultan Nazarbayev – «aksakal» of the Turkic world, Vladimir Putin is a «dear friend».